Unification of approaches to assessing the quality and functional and technological properties of protein-containing products from processing legume raw materials - L. N. Rozhdestvenskaya; I. O. Lomovsky; O. V. Chugunova (Пищевые системы, 2025)
Legume seeds are a traditional food group with high nutrient density and sensory characteristics. A distinctive feature of legumes is their ability both to act as the main food ingredient and to perform the functions of a food additive. At the same time, there is no unity of approaches in the use of methods for determining the functional and technological properties (FTP) of legume ingredients in studies, which does not allow for a correct comparison of their results. The aim of the work is to summarize the existing analytical practices for studying the FTP of protein-containing products of processing legume raw materials (PCPPLRM), to theoretically substantiate a set of indicators for a unified comprehensive system for assessing their quality and properties. A unified system is understood as a set of methods with high potential for subsequent standardization and the possibility of application in a wide range of tasks for determining the physicochemical properties and FTP of PCPPLRM. To solve the research tasks, a literature search and review were carried out using PubMed, Research Gate, Google Scholar and Mendeley Web. A full-text check of 143 articles was performed, resulting in a final selection of 60 articles that were subjected to careful study. The systematization was based on the most reliable and relevant articles of the last five years, which described in detail the features of the research methods used. The result of the work is a list of quality indicators and analysis methods that determine the duality in the use of PCPPLRM. A set and used ranges of critical parameters that require unification to obtain comparable data were identified: temperature, pressure, pH, time and speed of whipping and centrifugation. The use of unified methods for determining FTP will allow for an adequate comparison of PCPPLRM and the full use of their potential.